PEMBAGIAN BANTUAN SEMBAKO OLEH DOSEN DAN GEREJA BETHEL INDONESIA KEPADA MASYARAKAT SEKITAR GEREJA - Tony Suhartono; Intan Suriyanti; Sanjay Nadeak; Andre Djaafar; Tahan Sitanggang (JURNAL BEATITUDES, 2022)
The Covid-19 pandemic has impacted almost all aspect of human life, not just in Indonesia, but the entire world. Expecially in Batam, the impact of the pandemic has greatly affected the people of Batam physically, mentally, and financially. It was during the lockdown that the effect was strongly felt. The Pandemic which took place in early 2020 until the end of 2021 (almost 2 years) had hit Batam severely to the point of the local government had to carry out the distribution of basic necessities to people who were in need. It was not just the basic needs, there were many other things that were carried out. The lecturers at the Tabgha Theological Seminary saw this as an opportunity to get involved and surely would not want to pass up this chance. By collaborating with the Indonesia Bethel Church of Tabgha Batam Center (GBI Tabgha Batam Centre), they gather the basic needs and distributed them to the local community who were in need. They collected data to determine who was entitled to receive the aid. They have requested the GBI Tabgha Batam Centre and the Local Community facilitator Leader (RT/RW) to provide with the church’s member and the local people data who were badly affected by the pandemic. It was very necessary to be able to help each other. The strong should help the weak, those who live in abundant should help to those who are in need. Such help were carried out by the the Tabgha Theological Seminary Lecturers.